Analisis Sistem Penyimpanan Arsip Dinamis pada Divisi General Ledger Accounting PT KPN Plantation (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
In this era of ongoing digitalization, the use of information technology in records management is becoming increasingly crucial to ensure work efficiency and effectiveness. This study aims to examine the implementation of a dynamic archive storage system in the General Ledger Accounting Division of PT KPN Plantation. Specifically, this study identifies the obstacles encountered and analyzes the efforts made to overcome these challenges. Using a qualitative approach, primary data was collected through observation, interviews, and documentation studies with informants from General Ledger Accounting employees. Data analysis was carried out through a series of processes, including data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that although the stages of archive management have been carried out systematically through a combination of physical procedures and digitization using E-Archive, its implementation still faces significant obstacles. The problems identified include managerial aspects such as high transaction volumes that cause document backlogs and space limitations, technical aspects such as the instability of the E-Archive system, and limited human resources with expertise in archiving. Collectively, these obstacles reduce the effectiveness and efficiency of the system, requiring a comprehensive and integrated improvement strategy to achieve reliable and sustainable archive management